Le national à distance. Circulation de normes et réécriture du politique de la Tunisie - Stéphanie Pouessel (L’Année du Maghreb)
This article questions the body politic and the offshore sources of national policies. The post-2011 political scene heralded an overhaul of parliamentary and governing elites. “Expatriate Tunisians», representing 10% of the Tunisian population, were included in the democratic process that followed the fall of Z.A. Ben Ali through participation in the election of 18 representatives to the National Constituent Assembly. Whether students residing abroad, expatriate workers, children of mixed Tunisian couples, political exiles or descendants from prominent political families in exile, such «national but remote» expatriates represent a wealth of potentially mobilisable outside social and political experience available to the practice of politics in Tunisia. This article proposes a close study of these deputies in the National Constituent Assembly (NCA), and an analysis of the exchange of standards mobilized for the reorganization of Tunisian politics. The transfer of experiences gained in other national contexts with respect to certain political and social issues is a game of modulation and reconfiguration in view of domestic constraints. The experience of such agents mediating between the shores of experience, and their political acculturation in the conception and practice of politics will have a distinct effect on constitutional processes. As we shall see, the experience of these representatives can have an inhibiting effect on the participation of local Tunisians: ascribed to their foreignness, the linguistic dissonance experienced with the newly “repatriated” clearly illustrates this tension. Such new policy spaces challenge the political hegemony of the exclusively national. Henceforth, migration appears as a constitutive element of the national identity, and no longer as an emanation of a class of citizens based elsewhere. The national can no longer serve as the exclusive prism of nationality; rather, the national has become an exchange of ideas that by nature blurs the traditional limits of cultural identity.